PELATIHAN KETERAMPILAN PENGELOLAHAN MANIK-MANIK UNTUK PENINGKATAN KETERAMPILAN & JIWA WIRAUSAHA PADA SISWA SMPN 153 JAKARTA - Simangunsong, Nauma Sari; Vivi Marshandha Amelia Sagita; Muhammad Farhan Mufti; Muhammad Fadhil; Qamara Zahra Fadilah; Arif Murti Rozamuri (LPPM UNINUS, 2024)
The need for entrepreneurial skills encourages individuals to demonstrate their creativity beyond the academic field. Over time, creativity will be tested as a determinant of new innovations. In response to this issue, this training aims to enhance the skills of female students in making bead crafts at SMPN 153 Jakarta. This training uses the Participatory Action Research (PAR) method, involving the participation of several students from SMPN 153 Jakarta to understand and engage in an activity. This training successfully increased the students' creativity in making bead crafts by turning them into useful tools for daily needs. As a result, the participants gained knowledge and experience in crafting and improved their skills. This activity also became a venue for exchanging ideas and inspiration, creating a collaborative atmosphere. Keywords: Beads, Skills, Entrepreneurship, Creativity, Crafts